Evaluation of bioresorbable polymers as potential stent material—In vivo degradation behavior and histocompatibility. Issue 1 (1st September 2016) - Liao, Lan; Peng, Cheng; Li, Suming; Lu, Zhiqian; Fan, Zhongyong
ABSTRACT: A PLLA‐TMC‐GA terpolymer of 90/5/5 molar ratio was synthesized by ring‐opening polymerization ofl ‐lactide (LLA), trimethylene carbonate (TMC), and glycolide (GA), using stannous octoate as initiator. In vivo degradation of the obtained terpolymer and a composite made up of the terpolymer matrix reinforced by PLLA‐GA fibers was realized by subcutaneous implantation in rats for 9 months, in comparison with PLLA homopolymer and PLLA‐TMC copolymer of 95/5 molar ratio. The terpolymer shows ideal degradation profile because it is expected to maintain relatively high radial support for 3 months and lose its mechanical properties in 3 to 6 months inferred from molar mass changes. Increase of crystallinity and LLA content in the terpolymer and composite is observed during degradation. According to the gross observation and H&E staining appearance, all samples present good tissue compatibility. These results suggest that the terpolymer is promising for uses as fully biodegradable vascular scaffold. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44355. Abstract :